KARAKTERISTIK BATU KORAL UKURAN 25 MM DAN BATU KORAL GRADASI MENERUS PADA CAMPURAN BETON - Prasetia, Bayu (KURVA S JURNAL MAHASISWA, 2014)
Bayu Prasetia, 11.11.1001.7311.042. The Characteristics Of 25 MM Coral Stone  And Continuous Gradation Of Coral Stone On Mixed Concrete. Final Project of Civil Engineering Department of The Universitas 17 Agustus 1945. Samarinda. Gradation grain size of the aggregate which is a concrete filler material must comply with - the provisions in force. Coarse aggregate must be hard, clean from organic matter, free from chemical absorption properties and graded in a way that can be used as an intact concrete, homogeneous and dense. One area that holds the potential aggregate that has not been used optimally is in the District Kaliorang. The research objective was to determine the characteristics of continuous gradation of coral stone and the 25 mm coral stone using material from Kaliorang as aggregate. This study used SNI 03-2847-2002 conducted in the laboratory with a continuous gradation of stone size and the 25 mm of stone size. The manufacturing of test specimens used a mold cube size of 15 x 15 x 15 cm, the total sample is 30 to 60 pieces continuous gradation and 30 to size 25 mm. From the compressive strength of concrete test, the crushed concrete mixtures obtained with the use of coral Kaliorang for 28 days for continuous gradation is 195.78 kg / cm², while the compressive strength of concrete targeted (f'cr) = 225 kg / cm² and the use of stone coral Kaliorang for ages 28 days to 25 mm size is 179.60 kg / cm², while the compressive strength of the targeted (f'cr) = 225 kg / cm².